2018
DOI: 10.4269/ajtmh.17-0293
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Infection Induces Pannexin-1 Channel Opening in Cardiac Myocytes

Abstract: , the etiological agent of Chagas diseases, invades the cardiac tissue causing acute myocarditis and heart electrical disturbances. In invasion, the parasite induces [Ca] transients in the host cells, an essential phenomenon for invasion. To date, knowledge on the mechanism that elicits transients of [Ca] during the infection of cardiac myocytes has not been fully characterized. Pannexin1 (Panx1) channel are poorly selective channels found in all vertebrates that serve as a pathway for ATP release. In this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Otherwise, the Panx1 channel is selective for chloride ions and exhibits no ATP permeability when stimulated simply by depolarization to positive potentials or the C-terminal is cleaved by proteolysis [38]. Since we found increased Panx1 channel activity and increase in ATP release in cells infected with T. cruzi [11], it suggested that under this condition the Panx1 channel does not undergo proteolysis and adopt the large channel configuration [11,38]. In addition, it has been described that Panx1-based channels are regulated by mechanical stress [39].…”
Section: Gap Junction Channelsmentioning
confidence: 63%
See 4 more Smart Citations
“…Otherwise, the Panx1 channel is selective for chloride ions and exhibits no ATP permeability when stimulated simply by depolarization to positive potentials or the C-terminal is cleaved by proteolysis [38]. Since we found increased Panx1 channel activity and increase in ATP release in cells infected with T. cruzi [11], it suggested that under this condition the Panx1 channel does not undergo proteolysis and adopt the large channel configuration [11,38]. In addition, it has been described that Panx1-based channels are regulated by mechanical stress [39].…”
Section: Gap Junction Channelsmentioning
confidence: 63%
“…In 2018, we found that H510 strain of T. cruzi increased the Panx1 channel activity in rat neonatal cardiomyocytes at 1 hour postinfection [11]. Interestingly, the increased pannexon activity induced by the parasite was directly related to an elevated ATP release [11].…”
Section: Pannexinsmentioning
confidence: 96%
See 3 more Smart Citations